Porous ZnO nanorod for targeted delivery of doxorubicin: in vitro and in vivo response for therapeutic applications - Mitra, Shouvik; Subia, B.; Patra, Prasun; Chandra, Sourov; Debnath, Nitai; Das, Sumistha; Banerjee, Rahul; Kundu, Subhas C.; Pramanik, Panchanan; Goswami, Arunava (Journal of Materials Chemistry, 2012)
Cancer cell specific targeted delivery (TDD) by porous nanocarrier is on a high role. Here in a simple route for the synthesis of porous ZnO nanorods (ZnO) has been demonstrated. ZnO expressed very high surface area of 305.14 m(2) g(-1) (S-BET) and uniformly distributed pores of 5 nm. In continuation ZnO has been fabricated with 3-aminophosphonic acid followed by folic acid to yield folate conjugated porous ZnO nanorod (ZnO-FA). High surface area, uniformly distributed pores on its surface make the nanocarrier suitable for high drug loading (88%) of the anticancer drug doxorubicin (DOX). A pH triggered drug release was observed with minimum release in pathophysical conditions. In vitro efficacy of DOX loaded ZnO-FA (ZnO-FA-DOX) has been evaluated against breast cancer cells MDA-MB-231, which is not possible alone by DOX or ZnO-FA. Targeted scaffold with pendant -NH2 group has been covalently bonded with fluorescent dye (RITC) for cellular uptake and imaging studies in MDA-MB-231 cells; the possible pathway for cancer regression has also been evaluated. Even in vivo acute and intravenous toxicological evaluation on murine model system complemented biocompatibility of ZnO-FA in TDD. All together we have collaged a template free synthesis of porous ZnO nanorod, successful targeting on to cancer cells, high drug loading, pH triggered drug release, in vitro efficacy of ZnO-FA-DOX against MDA-MB-231 cells and in vivo compatibility as well. We envisioned the future prospect of porous ZnO nanostructures in TDD.

Mechanical downsizing of a gadolinium(iii)-based metal-organic framework for anticancer drug delivery - Kundu, Tanay; Mitra, Shouvik; Patra, Prasun; Goswami, Arunava; Diaz, David Diaz; Banerjee, Rahul (Chemistry-A European Journal, 2014)
A Gd-III-based porous metal-organic framework (MOF), Gd-pDBI, has been synthesized using fluorescent linker pDBI (pDBI=(1,4-bis(5-carboxy-1H-benzimidazole-2-yl)benzene)), resulting in a three-dimensional interpenetrated structure with a one-dimensional open channel (1.9x1.2nm) filled with hydrogen-bonded water assemblies. Gd-pDBI exhibits high thermal stability, porosity, excellent water stability, along with organic-solvent and mild acid and base stability with retention of crystallinity. Gd-pDBI was transformed to the nanoscale regime (ca. 140nm) by mechanical grinding to yield MG-Gd-pDBI with excellent water dispersibility (>90min), maintaining its porosity and crystallinity. In vitro and in vivo studies on MG-Gd-pDBI revealed its low blood toxicity and highest drug loading (12wt%) of anticancer drug doxorubicin in MOFs reported to date with pH-responsive cancer-cell-specific drug release.
Keywords: ball-milling; doxorubicin; drug delivery; metal-organic frameworks; nanocarriers